PENGARUH PENGGUNAAN MEDIA GAMBAR TERHADAP MOTIVASI BELAJAR SISWA KELAS VII DALAM MATA PELAJARAN SENI BUDAYA(SENI RUPA) DI SMPN 3 LEMBAH GUMANTI KABUPATEN SOLOK - ELIDAWATI, Dr. Ramalis Hakim,M.Pd, Drs. Wisriarman, M Pd (Serupa The Journal of Art Education, 2014)
This type of research is experimental , with a pre - design study testpost -test control group design . The population of this entire class VII students of SMP Negeri 3 Gumanti valley and the sample is VII2 class as a class that is used as the experimental and control classes VII5 , purposive sampling technique sampling.Teknik using questionnaire data collection and data analysis using t - test .The results of the study that there are significant portrait drawing mediause against class VII student motivation subjects of cultural arts ( visual arts ) at SMP N 3 Valleys Gumanti . It can be known after the price obtained test statistic t t t 2.28 while the table is 1.999 , which means t count > t table ( 2.28 > 1.999 ) . Thus , the more often teachers use media images to the student in the learning process students' motivation will be increased .Can be described students who earn the use of media images of teacherswill increase learning motivation , otherwise if the teacher is not using media images in students can lead to decreased student motivation . This is due to the media image is one aspect that determines the effect of learning for students because of the media image serves to motivate students in belajar.Belajar is a change in attitude and behavior after interacting with learning resources .So it can be concluded that the more often teachers teach to the studentsusing the media image it will also increase the students' motivation to learn , and ultimately students learn well and seriously .Keywords :Learning Media , Media Image , Motivation , Learning Arts